(untitled) (Research, Society and Development, 2023)
Sexually Transmitted Infections (STIs) are characterized by diseases whose main form of transmission is the sexual route, among them syphilis and HIV are a major public health problem. The high rate of STIs is correlated with the precariousness of sex education in the general population and insufficient health services. During the advent of the COVID-19 pandemic, there was a delay in the diagnosis of chronic diseases, STIs, in addition to other causes. In view of this, the study proposes to analyze the possible impact of the pandemic on the profile of cases and actions to combat STIs in a municipality in the semi-arid region of Piauí and its macro-region. In addition to identifying the age profile and gender most affected during the study period. This is a retrospective and descriptive epidemiological study with data from compulsory notification of the incidence of STIs (syphilis and HIV) in the pre-COVID-19 pandemic period (2017 to 2019) and during the COVID-19 pandemic (2020 to 2021). ) granted by the Testing and Welcome Center (CTA) of Picos. Based on the data collected, a significant drop in the diagnosis of HIV and syphilis can be observed, provided by the period of greater tension and lack of knowledge about COVID-19 in 2020. In addition, a higher incidence was identified in males, in the adult age group and also a decrease in the number of educational activities carried out by the CTA. Through the study, it can be concluded that underreporting during the pandemic period may have repercussions in the future for delaying the diagnosis and management of the patient and the reduction of educational activities, making it difficult to spread information.